Toxoplasmosis in HIV and non HIV prisoners in Malaysia - Angal, L.; Lim, Y.A.; Yap, N.J.; Ngui, R.; Amir, A.; Kamarulzaman, A.; Rohela, M. (Malaysian Society for Parasitology, 2016)
This is the first Malaysian study to determine the trend and risk factors of Toxoplasma gondii infection in HIV and non-HIV among prisoners in terms of socio-demographic and behavioural characteristics, clinical presentations and haematological distributions. Blood samples from 303 participants, comprising 133 HIV positive and 170 HIV negative inmates were collected in EDTA and plain tubes. Two mls of each blood sample in plain tubes were centrifuged at 1500 rpm for 10 minutes and the sera obtained were subjected to ELISA for detection of Toxoplasma IgM and IgG antibody towards Toxoplasma antigen. Seropositive samples for Toxoplasma IgM or both Toxoplasma IgM and IgG were further tested with Novalisa Toxoplasma gondii IgG avidity test to rule out acute from latent infections. Blood in EDTA tubes were sent to Clinical Diagnostic Lab (CDL), University Malaya Medical Centre (UMMC), Kuala Lumpur for complete blood count and differential count analysis. Overall seroprevalence of anti-T. gondii antibodies was detected in 41.9% (127 out of 303) of the participants. Anti-T. gondii antibodies was detected in 63.2% (84 out of 133) of HIV positive subjects and in 25.3% (43 out of 170) of HIV negative subjects. Seroprevalence of anti-T. gondii antibodies was significantly higher in HIV positive than in HIV negative subjects (OR = 5.06; 95% CI = 3.09-8.30; p < 0.001). The rate of T. gondii seropositivity increased significantly in those aged 40 years and above, HIV positive individuals and those with history of drug abuse. White blood cells (WBCs), neutrophils and basophils counts decreased significantly in those infected with Toxoplasma. Creating awareness about T. gondii infection and follow-up of their status is recommended. Moreover, screening of T. gondii infection in HIV-infected individuals should be considered for better treatment and management, including control and prevention.